SIMBOL TRI MURTI DALAM PAYAS AGUNG PENGANTIN BALI - Ida Ayu Gede Prayitna Dewi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2018)
Balinese fashion and dress is one part of Balinese culture with elements of art that have existed in antiquity. The kings of Bali of his day have introduced a distinctive dress culture in their respective regions of power. Some types of Balinese have similarities and differences in forms such as Payas Agung Karangasem, Buleleng, Tabanan, and Badung. Payas Agung The Bali Bridal used to be a dress for the King and queen, but over time now Payas Agung Bridal Bali is used for the wedding of Balinese people in general. The emergence of new make-up artists has made a positive impact in the development of Makeup in Bali, but a study that can be used as a guideline for the tradition of makeup and the value of philosophy is not lost and well preserved. This research is a qualitative type with the theory of symbols, aesthetic theory and religious theory. The research techniques are conducted by observation and interviews, document studies. The results obtained are Cempaka flowers and kenanga is a symbol of Tri Murti in Payas Agung Bridal Bali is placed on the head decoration, where this section is the most purified as the embodiment of offerings to Ida Sang Hyang widhi Wasa. The value contained and the influence of this symbol on the bride is as a form of beauty and Taksu.